Manifistations of intertextuality in the poetry of mohammed Ibn Abd El-Rahman Al-Dessi ¨diwan minna alhanan almanan¨ as a model - chaki, kamal; boutemedj, habiba (El Omda in Linguistics and Discourse Analysis, 2022)
There are many literary and artistic phenomena that are remarkable for stadying in the poetry of mohammed bin abd elrahman al dissi, which eall for pouse, study, contemblation, and aesthetic taste. Any ambiguity in it, then we will address the manifistatios of intertextuality in ¨al-dessi ¨ from the intertextuality of the holy Qur'an and the noble madith, and intertextuality with the old arabic poetry, and the new in this study is the blog in which it was applied, which is ¨the diwan of minna alhanan almanan¨ wich was distinguished by many artistic pgenomena including intertextuality